Determinants of marketed quantities of potato in tete province of Mozambique - Sandramo, Paulino Bartolomeu; Edriss, Abdi-Khalil (Canadian Journal of Agriculture and Crops, 2023)
In Mozambique 88% of the area allocated to potato production comes from Tete province, mainly on the districts of Angonia and Tsangano, and no studies have evaluated the determinants of the marketed quantities of this food crop, in this region. Hence, this study addressed this knowledge gap. The study used primary data. The primary data were obtained in February 2021 through the administration of the structured questionnaires to 453 smallholder potato farmers in Angónia and Tsangano districts. Descriptive statistics and a quantile regression model were the tools applied to analyze data. Results showed that the area allocated to potato production, cost of fertilizer per hectare, and cost of hired labour per hectare were significant at 1% confidence interval with volume sales of potatoes at all three levels of median studied. These are indications that an increase in any of these variables would increase the productivity of potatoes and hence the quantities available for market. Some of the constraints reported by the potato farmers were incidence of pests and diseases (100%), lack of credit access (100%), lack of certified seed (100%), lack of collective action on setting price (100%), inadequate storage materials (100%), poor road quality to access markets (79%), lack of funds to hire labour (36.2%), low level of extension services (36.9%), inadequate price information (17.9%) and inadequate fertilizer application (2%). To increase potatoes productivity, condition to increase marketed quantities, certified seeds, fertilizers and good storage materials should be made available to potato farmers.